A Compact Planar UWB Antenna with Triple Controllable Band-Notched Characteristics - Chaabane Abdelhalim; Djahli Farid (International Journal of Antennas and Propagation)
A modified compact planar ultrawideband (UWB) monopole antenna with triple controllable band-notched characteristics is presented in this paper. The proposed antenna consists of a modified stair cased V-shaped radiating element and partial ground plane. The triple band-notched characteristics are achieved by embedding two different vertical up C-shaped slots with a vertical down C-shaped slot in the radiating patch and in the ground plane, respectively. Besides, the bandwidth of each rejected band can be independently controlled by adjusting the dimensions of the corresponding band notched structure. The proposed antenna with rejected bands characteristics is successfully simulated, prototyped, and measured. The measured results show that the antenna operates until upper 11 GHz for voltage standing wave ratio (VSWR) is less than 2, and exhibits bands rejection of 1.6–2.66 GHz (49.76%), 3-4 GHz (28.57%), and 5.13–6.03 GHz (16.12%). Moreover, the proposed antenna shows a near omnidirectional radiation patterns, stable peak gain, and with small group delay and transfer function variation on the whole UWB frequency range except in the notched frequency bands, which makes it suitable for being used in the future UWB applications.